Reliability Evaluation of Power Electronic Inverter Using Cutset Approach - Palthur Shashavali; Sankar, V. (International Journal of Integrated Engineering, 2024)
The development of PV systems for the generation of renewable energy has been gaining a lot of importance in present-day research. Moreover, probabilistic analysis of the various configuration of PV cells, Power Electronic converters, etc. has been considered as the potential area of research with the appropriate assumptions. Evaluation of Basic Probability Indices (BPI) and Probabilistic Measures (PM) of an inverter configuration has been dealt with in the literature by considering the failure of all components will lead to inverter failure, treating all such components in series from Probabilistic Logic Diagram (PLD). However, the evaluation of BPIs and PMs has not been dealt with considering the operating strategies of the inverter. In this paper, it is proposed to deal with the evaluation of the BPIs and PMs for single-phase full-bridge inverter with R and R-L Load conditions and the results of the proposed methods using cutsets will be compared with an existing method.